Effectiveness of Gamification-Based Learning Application to Prevent Bullying Behavior in Elementary School - Oktavia, Noer Intan; Sutarno, Sutarno; Khotimah, Khusnul (Journal of Basic Education Research, 2025)
Purpose of the study: The purpose of this study was to assess the effectiveness of a gamification-based learning application in improving elementary school students' understanding and awareness of bullying prevention Methodology: A quantitative method using a quasi-experimental one-group pretest and posttest design was used. The study included 49 fifth-grade students from an elementary school in Malang. Data was gathered through pretest and posttest tools consisting of 25 questions. The pretest was administered before the intervention and the posttest after. Data analysis used IBM SPSS Statistics version 26, including normality tests, paired sample t-tests, and N-gain analysis to assess statistical significance and effect size. Main Findings: The results indicate that there was a significant improvement in students' understanding following the intervention. The average pretest score was 52.33, rising to 87.51 in the posttest. The paired sample t-test produced a significance value of p < 0.001, indicating strong effectiveness. Furthermore, the N-gain analysis yielded a value of 0.71 indicated high effectiveness. Therefore, the gamification-based application serves as a valuable educational tool for increasing bullying prevention awareness in elementary schools. Novelty/Originality of this study: This study provides the first empirical evidence for the effectiveness of a gamification-based mobile application specifically designed to teach bullying prevention to elementary school students. It bridges a critical research gap by quantitatively validating how tailored game mechanics (combines quizzes, mini-games, and role-playing scenarios) enhance comprehension of bullying dynamics and addressing the absence of methodologically rigorous evaluations in context-specific gamified learning for child safety education.